The Role of Hyperbolic Figures in Influencing Consumers on Social Media: A Stylistic Study on Shampoo Advertisements - Anna Gustina Zainal,; Ibrahim Besar,; Arie Fitria,; Fri Rezeki,; Prayoga Adi Pratama, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Online media is one of the communication tools used by producers to convey messages to consumers in advertisements. This study examines the impact of using hyperbolic language style on consumer behavior in shampoo advertisements on social media through a stylistic analysis. Hyperbolic language is a type of language style that involves exaggerated statements or claims, often used in advertising to create memorable and persuasive messages. The aim of this research is to explore how this language style influences consumer perception, engagement, and ultimately, purchase decisions. By analyzing Clear and Pantene shampoo advertisements in online media, this study identifies frequently used hyperbolic techniques and evaluates their effectiveness in capturing attention and enhancing consumer engagement. This research is a descriptive qualitative study. The data in this research consists of sentences and signs, while the data sources are Clear and Pantene shampoo advertisements in online media. The method used to collect the data is the observation method without direct involvement. The researcher collects and observes Clear and Pantene shampoo advertisements in online media. The collected data is then reduced, classified, verified, and tabulated based on its type. Subsequently, the researcher conducts data analysis based on stylistic theory. Additionally, the researcher interprets the data and draws conclusions. The results of the study show that hyperbole significantly enhances the emotional appeal of advertisements, leading to higher consumer interest and interaction. Moreover, hyperbole is used to highlight the advantages of Clear and Pantene shampoo products without disparaging or belittling other shampoo products. This study underscores the importance of stylistic elements in advertising and provides insights into how marketers can strategically use hyperbolic language to optimize their social media campaigns.